Performance analysis in a two-phase interleaved DC-DC boost converter with coupled inductors - Selami BALCI; Kadir SABANCI (International Journal of Applied Methods in Electronics and Computers, 2022)
In this study, the inductor current ripple and output voltage ripple of a two-phase DC-DC boost converter, circuit performance is investigated according to the direct/inverse coupling effect of the coupled inductors. The coupled inductors are modeled with both power electronics circuit and electromagnetic modeling and by using finite element analysis software (FEA). However, the high frequency inductor designs generally use air-gapped composite ceramic ferrite cores and are designed with powder core (Kool Mu) core structures that eliminate air gap requirements. Thus, the fringe flux, which occurs in the air gaps in ferrite cores and reduces the useful flux, and the bad effects such as overheating and electromagnetic noises (EMI/EMC) in the air gaps in high frequency switching are also reduced. Especially in interleaved power converter designs, the performances of coupled inductors affect the output parameters of the power electronics circuit. Considering energy efficiency and more compact circuit topologies, the modeling and simulation approach of high-frequency inductors using finite element analysis software, which is emphasized in this study, popularly and scientifically guides power electronics circuit designers.